NURCU: TURKEY’s CULTURAL ISLAMIC MOVEMENT - Khamami, Akhmad Rizqon (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This article explores the identity of Turkey's Nurcu Islamic movement. The movement was born in the midst of a harsh competition between the secular Kemalists and the political Islamists of Milli Gorus. The Nurcu movement redefined and reorganized aspects of modernization in Turkey. The Nurcu movement sought to integrate modernity and tradition. Education was the method for this integration. Modernization was put into action without sacrificing the nation's culture which was built on the Islamic foundation. Nurcu played the role of a moderate Islam. It takes part in the socio-political sphere in Turkey. During this study, I visited several Nurcu movement offices in Jakarta, Tangerang and Semarang. I interviewed a number of Nurcu movement activists, and I observed the movement's activities closely. For reading the collected data, I used the Marxian structural paradigm during which I took into account the social, political and economic context that surrounds it. This article assumes that the Nurcu movement's activities reflect a cultural movement.